Potential molecular targets for antituberculosis drug discovery - Dos Santos Fernandes, Guilherme Felipe [UNESP]; Chin, Chung Man [UNESP]; Dos Santos, Jean Leandro [UNESP] (My University, 2017)
Tuberculosis (TB) is an infectious disease caused by mycobacteria from the Mycobacterium genus, mainly by Mycobacterium tuberculosis (MTB). The World Health Organization (WHO) aims to reduce the number of TB cases worldwide in the coming years. Nevertheless, the increasing number of multidrug-resistant (MDR-TB) and extensive-drug resistance (XDR-TB) strains, and the ineffectiveness of the current treatment in latent tuberculosis are challenges to be overcome. In this review, we will demonstrate the recent advances in the tuberculosis drug discovery, focusing the research of new molecular targets in the Mycobacterium tuberculosis. Among the promising targets described herein, we highlight those, which act in different pathways in the mycobacteria, such as energy metabolism, cell wall biosynthesis, DNA synthesis, iron metabolism and transport through membranes. Furthermore, bioactive compounds discovered using phenotypic assays screening and validated through genetic approaches are also presented.
Potenciais alvos moleculares para o desenvolvimento de novos fÁrmacos antituberculose
Keywords: Medicinal chemistry; Molecular targets; Mycobacterium tuberculosis; New drugs; Tuberculosis